شرعی احکام میں" تلفیق" اور رخصتیں تلاش کرنے کا حکم: Order of Shariah in Talfeeq and Rukhsat - Hafiz Moazeem Shah; Dr. Ghulam Yousaf (MEI, 2023)
The followers of Shariah, in broader perspective, may be divided into two categories. One who have the qualification of Deduction from Quran and Sunnah or at least can fully understand the Ijtihadats (deductions) of the Imams and Mujtahideen. On the contrary there are those who lack this ability. Obviously the second one needs to follow the Ijtihadats (deductions) of the Imams and Mujtahideen. Then there is difference of opinions about different issues in shariah and those who do not have sufficient knowledge of shariah are, according to some of the Scholars, supposed to follow one Mujtahid or Imam. If every person is allowed to follow any Mujtahid or Imam in one issue and other Imam in another issue,this will cause one to follow one’s desire resulting in going far away from the truth and true spirit of sharia. Therefore some of the jurists are of the view that only one imam may be followed at least in one specific issue.But sticking to One Imam’s Ijtihadats (deductions) in every field of life and not allowing following another in any case may also cause difficulty for the people. Therefore, there is need to know the permissibility, limits and rules of “talfeeq” that is the process of joining or combining the different opinions of Imams in a specific issue. This article proceeds with definition of term تلفيق"” and the views of Fuqaha about it. The article also discusses different other Terms related to “Talfeeq” such as “إحداث قول ثالث” adopting a view other than adopted by classical Fuqaha (Scholars) in an issue and “الرخص”the optimal concessions. The study makes a comparative analysis of the views of scholars about the issues related to these Terms. The study came up with several results about the issues and terms mentioned above. issues related to these Terms. The study came up with several results about the issues and terms mentioned above.